A magyar királyok genealógiai ciklusa a leleszi premontrei kolostorkápolna középkori falképein - Jékely, Zsombor (Művészettörténeti Értesítő, 2012)
The Premonstratensian monastery of Lelesz, dedicated to the Holy Cross, was founded by Boleszló, the bishop of Vác (1188–1212). Patronage, however, was given over to the king, and later rulers in turn handed patronage of the monastery to their subjects. In 1214, the act of foundation was reinforced and the church of Lelesz consecrated. With the king's support, Lelesz became one of the wealthiest monasteries and an important place of authentication (locus credibilis). The new church of the monastery was built around the middle of the 14th century; in 1362 magister Johannes from Buda was contracted to build the tower. The chapel of Saint Michael, standing to the north of the church, and originally probably also serving as the chapter house, was built under the prior Dominicus of the Pálóci family (1378–1403). Around 1400, this new chapel was fully decorated with wall paintings. Much of the decoration – for example the frescoes of the vault – were destroyed when the chapel was re-vaulted in the 18th century. Still, a complete cycle of wall-paintings survives on the side walls of the chapel. On the south wall, there is a large, three-level image of the Last Judgment, with Christ in the mandorla dominating the scene, accompanied by the apostles on either side. In the lunettes of the north wall, two scenes can be detected: the one to the east depicts Saint Elisabeth of Hungary, while the other is possibly an image of Pope Urban V, in the company of cardinals. On the eastern walls of the chapel, apostles or prophets are depicted, framed by painted tracery. The focus of the paper is the series of figures depicted on the two lower zones of the north wall. As can be determined with the help of fragmentary inscriptions, these figures represent the kings of Hungary, starting from King Saint Stephen. The inscription gives the names of rulers and the number of years they ruled. The cycle is fragmentary, so we do not know exactly how many kings were depicted, but there is enough space for all the Hungarian sovereigns up until the then-current ruler, Sigismund (1387–1437). Such a cycle is unique from the territory of the medieval Kingdom of Hungary. Best parallel is provided by the cycle of initials in the Illuminated Chronicle (c. 1360, Széchényi National Library, Cod. Lat. 404), which also depict the pagan rulers of Hungarian prehistory, giving a complete genealogical cycle. Models of this cycle – just like that of the contemporary Luxemburg genealogy once on the walls of Karlstein castle in Bohemia – were provided by French manuscripts, especially the Grandes Chroniques de France. Emphasis in the cycle is not on individual kings, but on the unity and continuity of the line of Hungarian kings. One figure stands out: the first (badly damaged) ruler of the cycle is depicted enthroned. It is here proposed that the cycle starts with an image of the current ruler, King Sigismund. The style and iconography of the cycle make it a prime example of the International Gothic style, and these characteristic can be explained by the close connections of Lelesz abbey to the royal court.
Keywords: leles

Zsámbéki premontrei prépostsági templom - Szakács, Béla Zsolt (Magyar muvelodéstörténeti lexikon: középkor és kora újkor, 2012)
Keywords: zsámbék